OPTIMASI NILAI KEKASARAN PERMUKAAN PADA PROSES BUBUT CNC DENGAN METODE TAGUCHI L27 - Politeknik Perkapalan Negeri Surabaya (PPNS), Pranowo Sidi (Jurnal Rekayasa Mesin, 2014)
In this paper, the optimization of two response parameters surface roughness has been done by considering the cutting parameters as cutting speed, feed rate and depth of cut with dry conditions. Taguchi?s L27 orthogonal array and analysis of variance (ANOVA) are used individual optimization. The different levels of all machining parameters are used and experiments are done on F-1 Leadwell CNC lathe machine and the materials used for the experiment is steel St.60, with 200 mm length and 20 mm of diameter. From this research the optimized values contributing as cutting speed 200 m/menit,, feed 0.1  mm/rev and depth of cut 0,1 mm respectively. The optimum condition for combined effects was found Cs=3-F=1-DoC=1 and the optimal value of the surface roughness comes out to be 0.72 (mm). The optimum results are also verified with the help of confirmation experiments.Keywords : ?circularity?, ?cylindricity?, ?Taguchi?, ?Grey Relation Analysis?, ?CNC lathe?.